2020
DOI: 10.1136/oemed-2019-106049
|View full text |Cite
|
Sign up to set email alerts
|

Role of nocturnal light intensity on adaptation to three consecutive night shifts: a counterbalanced crossover study

Abstract: ObjectivesTo investigate how a standard ceiling mounted light-emitting diode (LED)-based bright light intervention affected alertness and neurobehavioural performance during three consecutive simulated night shifts, and timing of circadian rhythm after the shifts.MethodsTwenty seven participants (20 females, 21.4±2.1 years; mean±SD) worked three consecutive night shifts (23:00–07:00) under a full-spectrum (4000 K) bright light (900 lx) and a standard light (90 lx) condition in a counterbalanced crossover desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…However, our data did not show that PVT performance improved with consecutive night shifts. This is in line with a recent laboratory study (12) but in contrast to some other studies (30,31).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…However, our data did not show that PVT performance improved with consecutive night shifts. This is in line with a recent laboratory study (12) but in contrast to some other studies (30,31).…”
supporting
confidence: 92%
“…Several carefully executed laboratory studies show that timed exposure to bright light will facilitate adaptation of the circadian rhythm (3,11,12). However, adaptation to night work may lead to problems when the worker wants to adapt back to a normal day-night rhythm during time off or if the work schedule also includes day work.…”
mentioning
confidence: 99%
“…None of the previous studies investigating blue-enriched light assessed performance using DSST. However, in a recent study we found that performance on the DSST during simulated night work may be improved by nocturnal bright (4000 K; ∼900 lx) compared to standard (4000 K; ∼90 lx) light (Sunde et al, 2020). The DSST is sensitive to change in cognitive function, and both attention and working memory are required for optimal performance (Jaeger, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…The development of cost-effective light emitting diode (LED) technology, has provided new and flexible strategies for illumination of workplaces (Schubert and Kim, 2005). Standard ceiling mounted LED-luminaires can easily be installed and tuned to provide light of specific intensity (Sunde et al, 2020), and/or specific spectral distributions (Canazei et al, 2017). Thus, LED-based standard lighting set-ups need to be investigated in order to elucidate if these light sources can sustain performance during night work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation